THE RELATIONSHIP BETWEEN MOTHER PARENTING AND STUNTING ON CHILDREN AGED 1–5 YEARS AT SAMILI VILLAGE OF WOHA DISTRICTBIMA REGENCY IN2014 - Rahmat Shobri; M Karjono (SANGKAREANG, 2016)
Children aged 1-5 years or under five years children is a period in which children need food supply and nutrition in sufficient and adequate amount. In this period children are dependent on caring and mother parenting. Stunting is a problem which has not solved yet well. Based on Observation Nutrition Status (PSG) of Bima Regency in 2013 number of stunting in the amount of 36.99%. Stunting percentage at Woha district higher than Bima Regency that is 41.22% and the most number of stunting at Woha district in Samili village in the amount of 4.51%. This study was aimed to know the relationship between mother parenting and stunting on children aged 1-5 yearsat Samili village Woha district Bima Regency. Design of the study used survey analytic by cross sectional approach. Sample of the study is mothers who have children aged 1-5 years in the amount of 80 children, samples are taken by simple random sampling technique. Data collecting for parenting is done by interview toward mothers by questionnaires whereas for stunting on children is measured by anrotpometri based on Body length/Age or Body Height/Age. Data are analyzed by Chi-Square test. It is found that mother parenting at Samili village Woha district Bima Regency the most number respondent in sufficient category that is 40 mothers (50%) whereas stunting got 36 children (45%). Based on the result of data analysis showed probability value = 0.000 < a 0.05 meant there was a relationship between mother parenting and stunting on children aged 1-5 years. It is suggested to health attendances especially at Woha Public Health Center that the result of study can be valuable suggestion to determine intervention from health problem related to children.